The System of Self-Control of Electromagnetic Flow Meter - Baltušninkas, D.; Virbalis, J. A.; Vaikasas, R. (Elektronika ir Elektrotechnika, 2004)
The system of self-control of electromagnetic flow converter was created. It permits to control the stability of magnetic flux density in the duct of flow meter, the conductive sediments on the duct walls, the nonconductive sediments on electrodes and diminution of resistance between electrodes and ground potential. The stability of magnetic flux density is watched using the coil mounted on the surface of duct coaxial with magnetic field excitation coils. The conductive sediments on internal walls of duct are watched creating electric current between the electrodes and measuring the magnetic field on the surface of duct. The current of ultrasonic frequency is used. If the 1 % of current is flowed across the sediments the magnetic flux is varied of 11 %. The nonconductive sediments on electrodes and variation of resistance between electrodes and ground potential are watched creating the current between the electrodes and serial connected testing resistance and measuring the voltages of electrodes. Ill. 5, bibl. 6 (in Lithuanian, summaries in Lithuanian; English, Russian).